Core model of information technology governance system design in local government - Lanto Ningrayati Amali; Muhammad Rifai Katili; Sitti Suhada (Universitas Ahmad Dahlan, 2023)
Information technology governance (ITG) in local government is aimed at a good governance service framework. Reports produced as a result of the framework’s implementation help to improve governance’s openness, potency, and efficiency. A strong governance structure for adopting information technology (IT) is essential to ensuring its best utilization. The governance system should be properly managed to support the organization’s business. Therefore, this research aims to design an ITG system suitable for best practices using the control objectives for information technologies (COBIT) 2019 framework. The recommendations from the core model were processed based on the priority or competence level that local government entities use. It also produced a core model with capability levels of 1 and 2 that do not exist. The recommendation designated for the priority level of 3 was 17. The core model to be assigned a capability level of 4 urgently needed to be implemented was 23 core models.